1125-P: Do Non-HLA Genes Contribute to Age of Type 1 Diabetes Onset in Monozygotic Twins? - TRIOLO, TAYLOR M.; DONG, FRAN; BRONCUCIA, HALI C.; ONENGUT-GUMUSCU, SUNA; STECK, ANDREA; RICH, STEPHEN S. (Diabetes (New York, N.Y.), 2021)
Development of islet autoimmunity (IA) and type 1 diabetes (T1D) are associated with high-risk HLA class II loci as well as non-HLA genes. Monozygotic (MZ) twins have a high rate of concordance to T1D progression after the first twin develops T1D, especially for those diagnosed at a young age. We analyzed 52 T1D-associated non-HLA SNPs from ImmunoChip data in 159 MZ twins from the Twin Family Study: 79 twin probands with T1D and their 80 unaffected cotwins/triplets (including one set of triplets). Subjects are enrolled into the Twin Study when the proband is diagnosed with T1D and cotwins are followed longitudinally for the development of IA and/or T1D. In the cotwins, we analyzed the association between each of the non-HLA SNPs and IA after adjusting for HLA DR3/4*0302. In the twin probands with T1D, we used a linear regression model to evaluate the association of non-HLA SNPs with diabetes age at onset after adjusting for HLA DR3/4*0302. Median (IQR) age of diagnosis of the twin probands was 9.9 (5.4-13.9) years and age of last visit for the cotwins was 17.5 (11.2-26.7) years. Of the 80 cotwins, 41 (51.3%) developed IA and 15 (18.8%) were diagnosed with T1D. After adjusting for HLA DR3/4*0302, SNPs in CTLA4 (rs3087243), IL2 (rs4505848), IKZF1 (rs62447205), and INS (rs7111341) were found to be associated with the development of IA in cotwin subjects (all p<0.04). After adjusting for HLA DR3/4*0302, SNPs in CTSH (rs3825932) and TYK2 (rs34536443) were found to be associated with younger age of diabetes onset in the twin probands (p<0.05). In this cohort of MZ twins, non-HLA SNPs in CTSH and TYK2, which function both in the immune system and in beta cells, were associated with younger age of onset in the twin probands. Further studies are needed to evaluate the specific role of these genes for immunity and T1D onset.